Trauma, mental health, alcohol and help-seeking for Northern Ireland veterans. - Hitch, Catherine (Cranfield University, 2022)
Background – Northern Ireland (NI) veterans are a particularly hard to reach population. The Troubles’ legacy has caused many to self-marginalise, therefore, it is difficult to understand or support them as a population. NI as a nation has particularly poor rates of mental health, that is linked back to living with exacerbated, conflict-related trauma. There is a great likelihood that NI veterans have a large unmet mental health need, which is partly driven by elevated traumatic exposure, poor support services and a reluctance to seek support. This thesis set out to explore the relationship between trauma, mental health, alcohol and help-seeking for NI veterans. Method – The thesis adopted a sequential (quant, qual), integrated mixed methods approach. Ecological systems theory was used to frame and consider the findings across each study. Secondary NIVHWS data of 609 participants was used for the quant portion. The qual element consisted of primary data collection and IPA analysis from six participants. Quant - latent class analyses (LCA) was applied to endorsements of 16 trauma types and, separately, to six measures of mental health. LCA was assessing classes of comorbidity. Multivariate modelling was used to explore two relationships: the link between trauma class and mental health class; the link between mental health class and help-seeking. Other variables were included during modelling such as age, whether they were NI home-serve and attitudes towards help-seeking. Qual - a series of open-ended interviews were conducted with NI veteran residents, where questions focused on experience. Findings – The LCA of trauma exposure produced three classes; all classes had particularly high rates of conflict/combat related trauma. The mental health LCA elicited four classes, indicating nuance within the NI veteran community. Almost 40% had comorbid mental health and excessive alcohol use was associated with every class, suggesting risky drinking is not necessarily linked to poor mental health. Trauma class did not predict mental health class, which could have been due to uneven latent class sizes. Mental health class did predict help-seeking. The NI population tended to prefer medication over therapy. The interview data found two superordinate themes of “a lack of…” and “an abundance of…”, which were not polar as the sub-themes related to different concepts. The sub-themes found that NI veterans ‘lack’ mental health literacy awareness, have poor expectation of official support and a low sense of inward-facing appreciation. NI veterans had ‘abundant’ exposure to a range of extreme environments, many examples of navigating and challenging systemic ‘rules’ and a great deal of local support engagement. Ecological systems theory found that trauma, mental health and help-seeking was heavily impacted by systematic factors, with negative and positive influence sitting within different ‘systems’. Exo and macro systems leaned towards the negative whereas micro and meso had positive associations. Conclusion – NI veteran mental health and alcohol behaviour is dynamic. Poor mental health may not have local causes whereas excessive alcohol is more likely a reflection of NI and military culture. Support services are lacking in quantity and quality for NI veterans. The avoidance of therapy is driven by the wish to remain hidden and the need for non-self-disclosure, to avoid a trauma thereat. Yet many have engaged support seeking out of functional impairment and need. There was considerable anger towards those who officially arrange and administrate veteran support which has been partly buffered by the many local veteran support organisations. The utility of local support may be linked to taking a more ‘person centred’ approach. Several unique contributions were made via this thesis in respect of methods adopted and findings produced. The overall message was that more local support is needed but engaging with a self-marginalised population, to create and deliver appropriate assistance, is challenging.
Keywords: DSDS21; Help-seeking; Marginalised; Veteran; DSDS21 3MT